tRNA-derived small RNAs are embedded in the gene regulatory network instructing Drosophila metamorphosis - Shi, Junling; Xu, Jiaqi; Ma, Jun; He, Feng (Genome Research, 2023)
A class of noncoding RNAs, referred to as tsRNAs, is emerging with a potential to exert a new layer in gene regulation. These RNAs are breakdown products of tRNAs, either through active processing or passive cleavage or both. Since tRNAs are part of the general machinery for translation, their expression levels and activities are tightly controlled, raising the possibility that their breakdown products, tsRNAs, may provide a link between the overall translational status of a cell to specific changes in gene regulatory network. We hypothesize that Drosophila pupation, being a special developmental stage during which there is a global limitation of nutrients, represents a system in which such a link may readily reveal itself. We show that specific tsRNAs indeed show a dynamic accumulation upon entering the pupal stage. We describe experiments to characterize the mode of tsRNA action and, through the use of such gained knowledge, conduct a genome-wide analysis to assess the functions of dynamically expressed tsRNAs. Our results show that the predicted target genes are highly enriched in biological processes specific to this stage of development including metamorphosis. We further show that tsRNA action is required for successful pupation, providing direct support to the hypothesis that tsRNAs accumulated during this stage are critical to the gene expression program at this stage of development.
10.1101/gr.278128.123